2014
DOI: 10.1590/0104-530x1269
|View full text |Cite
|
Sign up to set email alerts
|

Alimentos inovadores: comportamentos neofóbicos e desafios para as indústrias do setor

Abstract: This article presents the results of an exploratory study that sought to analyze the attitude of 476 consumers in the city of Campo Grande about to their perception, motivation and tendency to food neophobia regarding the consumption of an innovative food product, the cheesy bread with carrot developed by SENAI/MSResumo: Este artigo apresenta os resultados de um estudo exploratório que pretendeu analisar a atitude de 476 consumidores do município de Campo Grande quanto à sua percepção, motivação e tendência à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although consumers are demonstrating a progressive change in behaviour and are more informed and more aware of their role in health care and acquisition of innovative products, there are still barriers that can influence them not to consume new products. To be consumed, food must break down important barriers of attitudes and behaviours of individuals, such as the body barrier and the symbolic aspects, proper to the eating act (GOULART & LUCCHESE-CHEUNG, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although consumers are demonstrating a progressive change in behaviour and are more informed and more aware of their role in health care and acquisition of innovative products, there are still barriers that can influence them not to consume new products. To be consumed, food must break down important barriers of attitudes and behaviours of individuals, such as the body barrier and the symbolic aspects, proper to the eating act (GOULART & LUCCHESE-CHEUNG, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sampling was nonprobabilistic, since people who could have less food neophobia, would tend to answer the questionnaire, which makes it difficult to generalize our results and interpret/apply them to the different Brazilian regions. Another important limitation is the lack of studies about edible insects in Brazil, with the exception of GOULART & LUCCHESE-CHEUNG (2014). We might attribute this fact to the low availability of edible insects in the Brazilian market and the lack of specific legislation to produce insect-based food.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the SES factors tend to influence the degree of food neophobia among consumers (e.g. Bäckström et al , 2003; Camarena et al , 2011; D'Antuono and Bignami, 2012; Fernández-Ruiz et al , 2013; Frank and Klaauw, 1994; Goulart and Lucchese-Cheung, 2014; Goulart et al , 2017; Jaeger et al , 2017; Mascarello et al , 2020; Meiselman et al , 2010; Sanjuán-López et al , 2011; Sogari et al , 2019; Tuorila et al , 2001). Income, which influences the composition of the individual's diet, can increase or decrease the probability of the individual having access to different foods in general (Sanjuán-López et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the importance of literacy, it was possible to see that respondents whose education level was higher than the 12th grade were more predisposed to increase the consumption of pulses instead of eating animal products. Generally, people with more years of schooling tend to have a higher quality diet, to seek information on healthier alternatives and to invest more in their health [39].…”
Section: Discussionmentioning
confidence: 99%